Cyber and Offline Dating Abuse in a Portuguese Sample: Prevalence and Context of Abuse - Caridade, S. (2020)
The increasing use of information and communication technologies (ICT) and networking has promoted the occurrence of different forms of victimization, specifically in terms of interpersonal interaction (e.g., cyberbullying or online risk-taking behaviour), which also includes cyber dating abuse (CDA). Some studies report that CDA is an extension of offline dating abuse (ODA). Because Portuguese studies in this area are scarce, this study aims to bridge this knowledge gap, seeking to investigate the extent and the context of CDA occurrence, and the relationship between CDA and all forms of ODA, i.e., physical, verbal–emotional and control. A convenience sample of 173 Portuguese adolescents and young adults was studied. This sample is mostly female (86.7%), has a mean (M) age of 25.36 years old and a standard deviation (SD) of 6.88 years of age. The results show that CDA and ODA among the Portuguese are very prevalent and related. Control (31.8 vs. 20.8%) and verbal–emotional ODA (26.7 vs. 20.2%) as well as control CDA (38.2 vs. 43.4%) were the most prevalent forms of abuse, either in terms of victimization or in terms of perpetration. The results also showed that CDA usually appears in a context of jealousy, also explaining control CDA and CDA direct aggression. A significant relationship between control CDA and CDA direct aggression and physical, verbal–emotional and control ODA was found. Experiencing control and verbal–emotional ODA are the main risk factors of control CDA victimization. This study allows to lay the groundwork for further research on dating victimization and perpetration through ICT, and has important practical implications at the level of Portuguese prevention strategies and intervention policies, thus emphasizing the role of the official authorities and the law itself.